Jazz improvisation in the style of John Coltrane. Case study: Epistrophy by Thelonious Monk / Izaad Amir Salamon - Salamon, Izaad Amir (2009)
The purpose of 111: study is to gain knowledge on the subject matter of the improvisation in the style of John Coltrane; to understand the ability of improvising jazz tune by referring one great jazz player. This process can enable one to become a more established and highly evolved improviser. Also, Jan Educators can increase their skills and knowledge base from which to use. By transcribing and playing along with the master’s solos an aspiring artist can readily absorb the time feel of me master being studied, the stylistic difference of the master, and the masters’ use of harmonic language. These items in particular can only be incorporated into an aspiring pianist’s performance by repeated listening and playing along with the recordings. By choosing selected jazz artists from important historical style development periods in jazz, one can distinguish an historical development of the art of improvising.